Evaluating business model for hotel industry by Grey-TOPSIS - Hsueh-Feng Chang; Shu-Hua Wu; Joyce Hsiu-Yu Chen; Chao-Hui Ke (Journal of Risk and Financial Management, 2021)
Businesses in the past few years have paid more and more attention to brand awareness. More and more branded hotels have launched sub-brands so as to access a new market, boost brand exposure and value, and attain new market niches. The purpose of the work was to explore, on the basis of the business model, factors affecting hotel sub-brand development in Taiwan. The modified Delphi method was firstly referred to. Next, a questionnaire was designed to serve as the basis of quantitative analysis. Third, experienced professionals from the hotel business were invited to participate in a questionnaire survey. The affecting factors of hotel sub-brand development were identified, and analysis data were generated. Grey-TOPSIS was employed to evaluate, calculate, and certify weight analysis and ranking of affecting indices of hotel sub-branding. The results explained that there are nine affecting factors for developing a hotel's sub-branding. They are channel, target customers, customer relationship, key activities, revenue model, key partners, value proposition, key resources, and cost structure. The top four are the most important ones. This finding, figured out by using soft mathematical methods, can provide a proper evaluating way for decision making by the hotel industry, which wants to establish its sub-brands.
Keywords: 330; business model; hotel industry; sub-brand; modified Delphi method; Grey-TOPSIS